Behavior of eccentrically-loaded tubed reinforced concrete short columns with high-strength concrete and reinforcement. (16th May 2023) - Li, Xiang; Liu, Jiepeng; Wang, Xuanding; Chen, Y. Frank
Highlights: The behavior of eccentrically-loaded CTRC columns with HSC and HSSR was investigated. Stress development of the HSSRs in CTRC columns was analyzed. The calculation method for the sectional strength of CTRC columns with HSC and HSSR is suggested and verified. Abstract: Compared with traditional reinforced concrete (RC) columns, the concrete ductility in tubed reinforced concrete (TRC) columns is significantly improved and higher ultimate compressive strain matching with the high yield strain of high-strength steel rebars (HSSRs) can be attained. Therefore, high-strength concrete (HSC) and HSSR are suitable and recommended for use in TRC columns. In this study, a total of twelve circular TRC column (CTRC) specimens with the concrete compressive strength of 81 MPa and rebar yield strength above 527 MPa were tested under eccentric loading. The investigated parameters include the diameter-to-thickness ratio of steel tube and load eccentricity, whose effects on the failure mode, load capacity, and ductility are described and discussed. A fiber-based finite-element model was established and verified for conducting parametric studies and investigating the stress development of the HSSRs in CTRC columns. The study results show that all test specimens fail in a ductile manner due to the tube confinement, and the load eccentricity is a primary factor affecting the failure location, load capacity, and ductility. With the parameters considered, the longitudinal rebars in the compression region yield before the column reaches its load capacity, indicating that the strength of HSSRs can be fully utilized. Based on the study results, calculation methods are suggested to determine the strength of eccentrically-loaded CTRC columns with HSC and HSSR.